Core tensions in luxury wine marketing: the case of Burgundian wineries. Issue 3 (20th August 2018) - Thach, Liz; Charters, Steve; Cogan-Marie, Laurence
Abstract : Purpose: The purpose of this research study is to identify differentiation factors Burgundian wineries use to distinguish their brand, and to determine whether these methods align or conflict with luxury marketing differentiation attributes. Design/methodology/approach: A qualitative methodology of 23 in-depth interviews with various sized wineries, as well as Burgundy market experts, was used. In addition, document analysis of websites and marketing materials was carried out along with a comprehensive review of the luxury marketing literature. Findings: Results show that Burgundian wineries have adopted some, but not all, of the luxury marketing differentiation attributes. Furthermore, there are a series of core tensions in the industry, including disagreement on using luxury marketing strategies. These findings contribute to the theory base in luxury wine marketing by illustrating how general luxury marketing attributes are used for wine brand differentiation. Originality/value: This research is the first of its kind to investigate luxury marketing differentiation practices of Burgundy wineries. The results are relevant for new wineries in Burgundy, as well as those in different regions of the world who desire to emulate, and perhaps come close to achieving, some of the luxury price points that certain Burgundy wine producers achieve. The information is also useful to assist related industries, such as food and spirits, which struggle in implementing luxury marketing strategies.